2002
DOI: 10.1161/01.cir.0000020682.73694.ab
|View full text |Cite
|
Sign up to set email alerts
|

Rho-Kinase Mediates Hypoxia-Induced Downregulation of Endothelial Nitric Oxide Synthase

Abstract: Background-Hypoxia-induced pulmonary hypertension is a major cause of morbidity and mortality. Hypoxia induces pulmonary vasoconstriction, in part, by decreasing endothelial nitric oxide synthase (eNOS) expression. The mechanism by which hypoxia decreases eNOS expression is not known but may involve Rho-kinase-induced actin cytoskeletal changes in vascular endothelial cells. Methods and Results-To determine whether hypoxia regulates eNOS expression through Rho-kinase, we exposed human saphenous and pulmonary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
331
5
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 433 publications
(354 citation statements)
references
References 35 publications
15
331
5
3
Order By: Relevance
“…105 Activation of the RhoA/ROCK pathway impairs NO bioavailability through inhibition of eNOS mRNA stability, eNOS posphorylation at Ser 1177 and the Akt/PI3K pathway and enhancement of eNOS phosphorylation at Thr495. [106][107][108] Endothelial function and hypertension in aging Y Higashi et al Several investigators have shown an interaction between the RhoA/ ROCk pathway and ROS. 109,110 Indeed, ROS induced by hyperglycemia enhances ROCK activity, leading to atherothrombogenesis through an increase in expression of plasminogen activator inhibitor-1 in vascular endothelial cells.…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%
“…105 Activation of the RhoA/ROCK pathway impairs NO bioavailability through inhibition of eNOS mRNA stability, eNOS posphorylation at Ser 1177 and the Akt/PI3K pathway and enhancement of eNOS phosphorylation at Thr495. [106][107][108] Endothelial function and hypertension in aging Y Higashi et al Several investigators have shown an interaction between the RhoA/ ROCk pathway and ROS. 109,110 Indeed, ROS induced by hyperglycemia enhances ROCK activity, leading to atherothrombogenesis through an increase in expression of plasminogen activator inhibitor-1 in vascular endothelial cells.…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%
“…Rho kinase is implicated in the pathophysiology of atherosclerosis (Miyata et al, 2000), myocardial infarction, and hypertension (Uehata et al, 1997). Activation of Rho kinase in endothelial cells under hypoxic conditions (Wolfrum et al, 2004) has been related to the mechanism responsible for the downregulation of eNOS during and after ischemia (Takemoto et al, 2002;Ming et al, 2002;Wolfrum et al, 2004;Jin et al, 2006).…”
Section: Rho Kinase (Rock)-inhibitorsmentioning
confidence: 99%
“…Since Rho-kinase inhibited the expression and activity of eNOS (Takemoto et al 2002;Sauzeau et al 2003), we examined the effects of fasudil on eNOS expression and activity in WT mice. As expected, long-term treatment with fasudil significantly enhanced eNOS phosphorylation, expression and activity (as evaluated by phosphorylated/ total eNOS) in the liver of HFD-fed WT mice (Fig.…”
Section: Fasudil Increases Enos Expression and Phosphorylation In Hfdmentioning
confidence: 99%
“…NO and Rho-kinase are known to negatively interact each other in vasomotor regulation (Takemoto et al 2002). Rho-kinase suppresses eNOS expression through destabilization of eNOS mRNA, while NO inhibits RhoA expression and Rho-kinase activity through the cGMP and protein kinase G (PKG) pathway (Sauzeau et al 2003;Kato et al 2012).…”
Section: Introductionmentioning
confidence: 99%